Birth Size in Neonates with Congenital Adrenal Hyperplasia due to 21-hydroxylase Deficiency - Dörr, Helmuth-Günther; Penger, Theresa; Albrecht, Andrea; Marx, Martin; Völkl, Thomas (JCRPE Journal of Clinical Research in Pediatric Endocrinology, 2019)
Objective: Classic congenital adrenal hyperplasia (CAH) secondary to 21-hydroxylase deficiency is characterized by increased prenatal adrenal androgen secretion. There are a small number of reports in the literature showing higher birth weight and length in CAH newborns.
CRIS-Team WoS Importer:2019-03-06